Association of IL-10-592 C > A /-1082 A > G and the TNFα -308 G > A with susceptibility to COVID-19 and clinical outcomes - Raghda E. Eldesouki; Rania M. Kishk; Noha M. Abd El-Fadeal; Rama I Mahran; Noha Kamel; Eman Riad; Nader Nemr; Safaa M. Kishk; Eman Abdel-Moemen Mohammed (BMC, 2024)
Abstract Background Variation in host immune responses to SARS-CoV-2 is regulated by multiple genes involved in innate viral response and cytokine storm emergence like IL-10 and TNFa gene polymorphisms. We hypothesize that IL-10; -592 C > A and − 1082 A > G and TNFa-308 G > A are associated with the risk of SARS-COV2 infections and clinical outcome. Methods Genotyping, laboratory and radiological investigations were done to 110 COVID-19 patients and 110 healthy subjects, in Ismailia, Egypt. Results A significant association between the − 592 A allele, A containing genotypes under all models (p < 0.0001), and TNFa A allele with risk to infection was observed but not with the G allele of the − 1082. The − 592 /-1082 CG and the − 592 /-1082/ -308 CGG haplotypes showed higher odds in COVID-19 patients. Severe lung affection was negatively associated with − 592, while positive association was observed with − 1082. Higher D-dimer levels were strongly associated with the − 1082 GG genotype. Survival outcomes were strongly associated with the GA genotype of TNFa. -308 as well as AGG and AAA haplotypes. Conclusion IL-10 and TNFa polymorphisms should be considered for clinical and epidemiological evaluation of COVID-19 patients.